The Impact of COVID-19 on Clinical Outcomes in Patients With Traumatic Brain Injury - Farnaz Mahdavi; Sima Fallah-Arzpeima; Zoheir Reihanian; Khatereh Asadi; Nooshin Zaresharifi; Roghaye Zare; Mohammad Ali Yazdanipour; Masoud Shabani Chobe (Caspian Journal of Neurological Sciences)
Background: Traumatic brain injury (TBI) is a leading cause of mortality and morbidity worldwide. COVID-19 can impact the central nervous system (CNS) and hematologic system and appears to affect clinical outcomes and the average cerebral hemorrhage volume (ACHV) in patients with TBI. Objectives: Our study focused on evaluating the effects of COVID-19 on clinical outcomes and the ACHV in TBI patients. Materials & Methods: In this study, we included TBI patients presenting to an academic trauma center in the North of Iran and categorized them into two groups: infected with COVID-19 and non-infected. A total of 128 TBI patients were identified during 19 months of the COVID-19 pandemic. Results: Road accidents account for 92.2% of TBI. Among different types of brain lesions, subdural hematoma (SDH) had a significant relationship with COVID-19 (P=0.043). Among patients, 13 (10.2%) were on anticoagulants, with no significant differences between the two groups. Among the COVID-19 patients, those who were anticoagulant users experienced a higher ACHV than those who did not use this medication (P=0.015). The two groups had no significant difference in the ACHV and mortality (P=0.758, P=0.601, respectively). The regression analysis indicates no statistically significant relationship between COVID-19 and ACHV (P=0.983) or between COVID-19 and the mortality rate of TBI patients (P=0.695). Conclusion: The study highlights that TBI patients with COVID-19 on anticoagulants show higher ACHV levels than those without, a pattern missing in non-COVID patients. This finding suggests a possible synergistic interaction between COVID-19 and anticoagulation, with COVID-19 potentially worsening coagulation disorders.